Characterization of a bacteriophage T4 mutant lacking DNA-dependent ATPase. - Behme, M T (1975)
A DNA-dependent ATPase has previously been purified from bacteriophage T4-infected Escherichia coli. A mutant phage strain lacking this enzyme has been isolated and characterized. Although the mutant strain produced no detectable DNA-dependent ATPase, growth properties were not affected. Burst sizes were similar for the mutant phage and T4D in polA1, recB, recC, uvrA, uvrB, uvrC, and various DNA-negative E. coli. UV sensitivity and genetic recombination were normal in a variety of E. coli hosts. Mapping data indicate that the genetic locus controlling the mutant occurs near gene 56. The nonessential nature of this gene is discussed.